PROBLEMATIKA PERJANJIAN KERJA SAMA DI BAWAH TANGAN ANTARA PERUSAHAAN SWASTA DAN INSTANSI PEMERINTAH - Rahmadania, Andi Wulan; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
Abstract: This study addresses legal issues in "under-the-table" agreements between private companies and government agencies in Indonesia, focusing on validity, enforceability, and breach risks. While legally binding, these agreements often lack notarization, weakening their evidentiary strength and increasing dispute potential when obligations are unmet. Analysis shows frequent payment delays due to government budget constraints and insufficient contract oversight, leading to defaults that burden the private sector. The study recommends stricter standardization, mandatory notarization, and explicit dispute resolution clauses to ensure legal certainty. These findings support more reliable, accountable public-private collaborations.Keywords: Agreement, Validity, Law, Government, Private